2005
DOI: 10.1177/095632020501600201
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Targets in HCV Therapy: Novel Strategy or Proven Practice?

Abstract: The development of novel antiviral drugs against hepatitis C is a challenging and competitive area of research. Progress of this research has been hampered due to the quasispecies nature of the hepatitis C virus, the absence of cellular infection models and the lack of easily accessible and highly representative animal models. The current combination therapy consisting of interferon-alpha and ribavirin mainly acts by supporting host cell defence. These therapeutics are the prototypic representatives of indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 138 publications
(188 reference statements)
0
8
0
Order By: Relevance
“…9). To overcome these limitations, a human hepatoma cell line (HuH7) was transfected with subgenomic HCV RNAs, called replicons ( Fig.…”
mentioning
confidence: 99%
“…9). To overcome these limitations, a human hepatoma cell line (HuH7) was transfected with subgenomic HCV RNAs, called replicons ( Fig.…”
mentioning
confidence: 99%
“…In contrast to clinical practice for hepatitis C-infected patients [7], the selection of host cell targets, which are leading to the generation of indirect antiviral drugs has no real history in HIV drug discovery. In the following sections, the authors summarize indirect anti-HIV targets, with a particular focus on CDK9.…”
Section: Host Cell Targets In Infectious Diseasesmentioning
confidence: 97%
“…• Currently, protein kinases are regarded as the largest drug target family of the human kinome and subject to extensive pharmaceutical interest [8][9][10] • As a consequence of point two, inhibition of protein kinases using small molecule inhibitors has turned into a general strategy in the field of targeted drug discovery [8] • Viruses encode many proteins that are substrates to host cell kinase phosphorylation such as the HIV proteins, Vpu and Rev (Table 1) • Viral proteins are not just substrates to host cell protein kinases, they also interfere with the activation and activity of kinases [7] The human serine/threonine protein kinase, cyclin-dependent kinase (CDK)9 is amongst those protein kinases that are hijacked by HIV (Table 1). In complex with the HIV protein Tat, CDK9/cyclin T1 is an essential factor of HIV replication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recent research has shown that intracellular cofactors are the most promising targets for the design of specific drugs that reduce the resistance to virus. 7 Several viruses require viral and host molecular chaperones for entry, replication and assembly, as well as for other steps in viral production. 8,9 Recently, Hsp90 was found to be able to bind to human FKBP8 and form a complex with HCV NS5A.…”
Section: Introductionmentioning
confidence: 99%